تقييم مهارات القائم بالاتصال لتحسين جودة التكوين - طابي ،سيدعلي; بيصار، عبد المطلب (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة إلى تقييم مهارات الاتصال لأستاذة المعهد الوطني المتخصص من وجهة نظر المتكونين المستفيدين من الخدمة على أساس تفعيل عملية الاتصال بين الأستاذ و المتربص نهاية كل مرحلة من أجل تحسين جودة التكوين . وخلصت هذه الدراسة إلى أن المهارات الاتصالية للأساتذة محل الدراسة تجمع بين مهارات اتصال اللفظية وغير اللفظية ، مهارات الإلقاء والحوار وتنظيم الوقت وكسب ثقة المتكونين مما يساعد على تحقيق جودة التكوين لمتربصي المعهد الوطني المتخصص المسيلة 01 This study aims to evaluate the communication skills of the professors of the National Specialized Institute from the point of view the staff benefiting from the service on the basis of activating the communication process between the professor and the trainee at the end of each stage in order to improve the quality of training . This study concluded that the communication skills of the professors under study combine verbal and nonverbal, communication skills, delivery and dialogue skills, organizing time, and gaining the trust of the students, which helps achieve quality training for the trainees of the National Specialized Institute, M’sila 01
Evaluate the skills of the contact person to improve the quality of training A study on trainees of the Accounting and Management Branch at the National Institute specialized in vocational training
مقال
Keywords: مهارات الاتصال; جودة التكوين; التكوين المهني; Communication skills; quality of training; vocational training